2023
DOI: 10.1002/pbc.30294
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacological interventions for managing sickle cell disease complications in children and adolescents: Systematic review with network meta‐analysis

Abstract: This study aimed to synthesize the evidence on the effects of disease‐modifying agents for managing sickle cell disease (SCD) in children and adolescents by means of a systematic review with network meta‐analyses, surface under the cumulative ranking curve (SUCRA) and stochastic multicriteria acceptability analyses (SMAA) (CRD42022328471). Eightteen randomized controlled trials (hydroxyurea [n = 7], l‐arginine [n = 3], antiplatelets [n = 2], immunotherapy/monoclonal antibodies [n = 2], sulfates [n = 2], docosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…However, as individuals age, various factors may intervene, influencing the symptomatic expression of SCD [ 10 ]. Individuals with SCA experience reduced red blood cell flexibility due to polymerization, resulting in rheological and biochemical alterations that impede blood flow, ultimately leading to vaso-occlusive crises (VOCs) [ 10 , 11 ]. Studies in genetic mapping and genome-wide association have identified specific genetic loci associated with SCA, including B-cell lymphoma/leukemia 11A (BCL11A), an Xmn1 variant located upstream of the hemoglobin subunit gamma 1 (HBG1), and the HBS1L-MYB intergenic region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as individuals age, various factors may intervene, influencing the symptomatic expression of SCD [ 10 ]. Individuals with SCA experience reduced red blood cell flexibility due to polymerization, resulting in rheological and biochemical alterations that impede blood flow, ultimately leading to vaso-occlusive crises (VOCs) [ 10 , 11 ]. Studies in genetic mapping and genome-wide association have identified specific genetic loci associated with SCA, including B-cell lymphoma/leukemia 11A (BCL11A), an Xmn1 variant located upstream of the hemoglobin subunit gamma 1 (HBG1), and the HBS1L-MYB intergenic region.…”
Section: Introductionmentioning
confidence: 99%
“…However, as individuals age, various factors may intervene, influencing the symptomatic expression of SCD [10]. Individuals with SCA experience reduced red blood cell flexibility due to polymerization, resulting in rheological and biochemical alterations that impede blood flow, ultimately leading to vaso-occlusive crises (VOCs) [10,11]. Studies in genetic mapping and genome-wide association have identified specific genetic loci associated with SCA, including B-cell lymphoma/leukemia 11A (BCL11A), an Xmn1 variant located upstream of the hemoglobin subunit gamma 1 (HBG1), and the HBS1L-MYB in- SCD can manifest in various clinical features, including abnormal eye growth in the retina (proliferative retinopathy), tissue death due to blocked blood flow (vascular necrosis), prolonged painful erection (priapism), dilute urine (hyposthenuria), episodes of severely reduced red blood cell production (aplastic crises), kidney problems (nephropathy), and lung disease [5].…”
Section: Introductionmentioning
confidence: 99%